Pemberdayaan Anak Kost di Pondok Winaya Kota Serang-Banten Melalui Pelatihan Bank Sampah - Irwanto (Universitas Lancang Kuning, 2021)
In the empowerment activities carried out by the men's boarding house, Pondok Winaya through training in handling waste disposal becomes an economic value for the residents of the male boarding house. This male boarding house is a boarding house whose occupants are all male who work as students of the University of Sultan Ageng Tirtayasa. Located in the Winaya neighborhood in Panancangan Village, Cipocok Jaya District, Serang City, Banten. Implementation of service on Tuesday, August 3, 2021 for one day. The service was carried out at the men's boarding house, Pondok Winaya, RT 03, RW 03, Panancangan Village, Cipocok Jaya District, which was attended by 20 participants. The research method used is a type of qualitative research with a descriptive approach. Data collection techniques by means of observation, discussion and interviews, while the data processing technique used is an interactive technique proposed by Milles & Huberman (1992). The results of the service obtained are that during the initial training activities, boarding house residents are given some discussion materials and enlightenment about the waste that is often disposed of which will be of economic value as well as training in sorting the types of waste. From the results of the activities, the service partners can increase the awareness of boarding children about cleanliness and beauty and can also sort out the types of waste according to their respective groups and apply a composter that will produce liquid and solid fertilizers that can be used as plant fertilizers that sell high in the Winaya environment. This activity was directly supported by the head of RT 03 and RW 03.